A stable hexaazaoctacene cruciform σ-dimer: dedicated to Professor Klaus Müllen on the occasion of his 75th birthday - Maier, Steffen; Jester, Fabian; Hoffmann, Marvin; Rominger, Frank; Freudenberg, Jan; Dreuw, Andreas; Bunz, Uwe H. F. (Advanced science, 2022)
Buchwald-Hartwig coupling of a triisopropylsilyl (TIPS)-ethynylated dibromo-N,N'-dihydrotetraazapentacene with 1,4-bis(TIPS-ethynyl)-2,3-diaminonaphthalene furnishes a dihydrohexaazaoctacene. Its oxidation with MnO2 results in a 7,7'-bi(hexaazaoctacenyl). In addition to eight TIPS-ethynyl groups, the bioctacene motif protects the azaoctacene subunits. The biazaoctacenyl displays a τ1/2 of > 5 d in dilute solution under ambient conditions. In the crystalline state it is persistent for > 10 months.
Online veröffentlicht am 27. Juli 2022
Gesehen am 08.12.2022
Keywords: Festschrift